IDNLearn.com offers a comprehensive platform for finding and sharing knowledge. Our platform provides accurate, detailed responses to help you navigate any topic with ease.
Sagot :
To find the standard form of the quadratic equation given its roots and a point through which the function passes, we need to follow these steps:
1. Identify the roots of the quadratic equation:
The roots given are [tex]\( x = 3 \)[/tex] and [tex]\( x = -1 \)[/tex].
2. Form the quadratic equation from its roots:
The quadratic equation can be expressed as:
[tex]\[ (x - 3)(x + 1) \][/tex]
Expanding this, we get:
[tex]\[ x^2 + x - 3x - 3 = x^2 - 2x - 3 \][/tex]
3. Include the leading coefficient [tex]\( a \)[/tex] since the quadratic could have a different scaling factor:
The general form of the quadratic equation becomes:
[tex]\[ y = a(x^2 - 2x - 3) \][/tex]
Here, [tex]\( a \)[/tex] is a constant that we'll determine using the given point [tex]\((1, -10)\)[/tex].
4. Use the given point [tex]\((1, -10)\)[/tex] to find [tex]\( a \)[/tex]:
Substitute [tex]\( x = 1 \)[/tex] and [tex]\( y = -10 \)[/tex] into the equation:
[tex]\[ -10 = a(1^2 - 2(1) - 3) \][/tex]
Simplifying inside the parentheses:
[tex]\[ -10 = a(1 - 2 - 3) \][/tex]
[tex]\[ -10 = a(-4) \][/tex]
Solving for [tex]\( a \)[/tex]:
[tex]\[ a = \frac{-10}{-4} = 2.5 \][/tex]
5. Substitute [tex]\( a \)[/tex] back into the quadratic equation:
[tex]\[ y = 2.5(x^2 - 2x - 3) \][/tex]
Distributing the [tex]\( a = 2.5 \)[/tex]:
[tex]\[ y = 2.5x^2 - 5x - 7.5 \][/tex]
Thus, the standard form of the quadratic equation is:
[tex]\[ y = 2.5x^2 - 5x - 7.5 \][/tex]
Therefore, the correct answer is:
[tex]\[ y = 2.5 x^2 - 5 x - 7.5 \][/tex]
1. Identify the roots of the quadratic equation:
The roots given are [tex]\( x = 3 \)[/tex] and [tex]\( x = -1 \)[/tex].
2. Form the quadratic equation from its roots:
The quadratic equation can be expressed as:
[tex]\[ (x - 3)(x + 1) \][/tex]
Expanding this, we get:
[tex]\[ x^2 + x - 3x - 3 = x^2 - 2x - 3 \][/tex]
3. Include the leading coefficient [tex]\( a \)[/tex] since the quadratic could have a different scaling factor:
The general form of the quadratic equation becomes:
[tex]\[ y = a(x^2 - 2x - 3) \][/tex]
Here, [tex]\( a \)[/tex] is a constant that we'll determine using the given point [tex]\((1, -10)\)[/tex].
4. Use the given point [tex]\((1, -10)\)[/tex] to find [tex]\( a \)[/tex]:
Substitute [tex]\( x = 1 \)[/tex] and [tex]\( y = -10 \)[/tex] into the equation:
[tex]\[ -10 = a(1^2 - 2(1) - 3) \][/tex]
Simplifying inside the parentheses:
[tex]\[ -10 = a(1 - 2 - 3) \][/tex]
[tex]\[ -10 = a(-4) \][/tex]
Solving for [tex]\( a \)[/tex]:
[tex]\[ a = \frac{-10}{-4} = 2.5 \][/tex]
5. Substitute [tex]\( a \)[/tex] back into the quadratic equation:
[tex]\[ y = 2.5(x^2 - 2x - 3) \][/tex]
Distributing the [tex]\( a = 2.5 \)[/tex]:
[tex]\[ y = 2.5x^2 - 5x - 7.5 \][/tex]
Thus, the standard form of the quadratic equation is:
[tex]\[ y = 2.5x^2 - 5x - 7.5 \][/tex]
Therefore, the correct answer is:
[tex]\[ y = 2.5 x^2 - 5 x - 7.5 \][/tex]
Thank you for using this platform to share and learn. Keep asking and answering. We appreciate every contribution you make. Thank you for trusting IDNLearn.com. We’re dedicated to providing accurate answers, so visit us again for more solutions.